WHY DON’T YOU COME OVER? – A DIFFERENT WAY TO PROMOTE ROMANIA - Patrut, Monica (Studies and Scientific Researches. Economics Edition, 2014)
Investing in the country brand represents a strategic priority as it consolidates the image and international reputation of the respective members. Although Romania started to invest in this long-term process in 1996, the promotional actions have lacked coordination and efficiency. The Romania’s country image is insufficiently shaped and the Country Brand Index study conducted in 2012 confirms it by placing our country on the last positions. We shall show in this study that by exploiting the collective intelligence principle and the involvement of the Net Generation’s representatives, many echoing campaigns can be created in the virtual environment. The country brand is being built rather by means of every individual’s involvement, by what we do and what we say every day. “Why Don’t You Come Over?” campaign, which has contributed in an unexpected way to improve Romania’s image by spreading humor in the virtual space, should show all actors responsible that there may be successful promotion patterns.